Cavitation studies on axi-symmetric underwater body with pumpjet propulsor in cavitation tunnel - Ch. Suryanarayana; B. Satyanarayana; K. Ramji; M. Nageswara Rao (International Journal of Naval Architecture and Ocean Engineering, 2010)
A pumpjet propulsor (PJP) was designed for an underwater body (UWB) with axi-symmetric configuration. Its performance was predicted through CFD study and models were manufactured. The propulsor design was evaluated for its propulsion characteristics through model tests conducted in a Wind Tunnel (WT). In the concluding part of the study, evaluation of the cavitation performance of the pumpjet was undertaken in a cavitation tunnel (CT). In order to assess the cavitation free operation speeds and depths of the body, cavitation tests of the PJP were carried out in behind condition to determine the inception cavitation numbers for rotor, stator and cowl. The model test results obtained were corrected for full scale Reynolds number and subsequently analyzed for cavitation inception speeds at different operating depths. From model tests it was also found that the cavitation inception of the rotor takes place on the tip face side at higher advance ratios and cavitation shifts towards the suction side as the RPS increases whereas the stator and cowl are free from cavitation.